Epidemiological and sociodemographic description of snakebite envenoming cases in Paraguay reported between 2015 and 2021 - Guillermo Sequera; Sofia Ardiles-Ruesjas; Edgar Sanabria; Victor Hugo Segovia Portillo; Lorena Jara Oroa; Viviana de Egea; Julio Alonso-Padilla; Irene Losada; María Jesús Pinazo (BMJ Public Health)
Introduction Snakebite envenoming (SBE) is a public health problem in Paraguay where the presence of 15 medically important snake species has been reported. Blessed with large forested areas, its economy largely relies on agricultural production which increases the exposure of outdoor workers to the morbidity and mortality of SBE. Lack of sufficient and accurate epidemiological data highlights the importance of drawing an updated picture of SBE burden in the country.Methods We performed a retrospective descriptive study on secondary SBE data reported to the national surveillance system between 2015 and 2021. We addressed the availability and quality of the data and assessed its epidemiological and sociodemographic burden in Paraguay over that time period.Results In total, 1651 cases of SBE were reported between 2015 and 2021 representing an average of 235 cases per year (3.33 cases per 100 000 population). Overall, young males (68%, n=1125) of productive age (25 years old, IQR 29) in agricultural and/or livestock settings (47%, n=653) were the most affected population. Departments with a higher number of notifications were San Pedro (12%, n=191), Caazapá and Alto Paraná (10%, n=163). Regarding data quality, variables about clinical outcomes, treatment administration and case management were the worst reported.Conclusion SBE is a public health issue that affects young workers in rural areas in Paraguay. It mostly remains unattended and improvements in its reporting need to be done in order to gain a better insight into both the health and social burden of this neglected disease.